PERLINDUNGAN HUKUM TERHADAP KONSUMEN ATAS KERUGIAN AKIBAT MEMBELI DAGING SAPI GLONGGONGAN - Anwar, Nuril; Latumahina, Rosalinda Elsina (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
The rampant circulation of glonggongan beef causes losses for consumers because they get a discrepancy in the quality of the beef so that it has an impact on the health and safety of consumers when consuming glonggongan beef. This study will examine the form of protection for consumers and the form of government responsibility related to the sale of glonggongan beef in traditional markets. This study uses a normative method, with a statutory approach and a conceptual approach to answer the formulation of the problem in this study. Based on the results of the research, the form of legal protection for consumers for quality discrepancies in glonggongan beef is in the form of compensation which includes products, treatment costs, medical costs and criminal prosecution. This form of legal protection for consumers is regulated in Article 19 of the Consumer Protection Law concerning the accountability of business actors and Article 8 of the Consumer Protection Law concerning prohibitions for business actors. In terms of the government's responsibility regarding the circulation of glonggongan beef, efforts are made to overcome it either with criminal law (Penal Efforts) or without criminal law (Non-Penal Efforts). In the penal effort, dispute resolution efforts are carried out through the courts by carrying out administrative and criminal prosecutions. In addition, the penal effort can also be carried out out of court through BPSK or LPKSM with 3 (three) settlement procedures, namely Conciliation, Mediation and Arbitration. Meanwhile, Non-Penal Efforts carried out by the government as a form of responsibility are by conducting outreach or outreach to the community, raids with other law enforcement officers, taking firm action and tightening supervision in the upstream sector, namely slaughterhouses